US-Panama Free Trade Agreement: What Is in It for Florida Agriculture? - Edward A. Evans; Fredy H. Ballen (EDIS, 2013)
On October 12, 2011, four years after it was agreed upon by both parties, the United States government signed into law the reciprocal US–Panama Free Trade Agreement (FTA)/Trade Promotion Agreement (TPA). The FTA provides US companies with better access to the Panamanian market and ensures that most US exports of consumer and industrial products to Panama will be accorded immediate duty-free privileges. The main elements of the US–Panama FTA as it relates to agricultural trade revolve around market access, agricultural export subsidies, safeguards, the sugar compensation mechanism, and sanitary and phytosanitary measures. This 11-page fact sheet was written by Edward A. Evans and Fredy H. Ballen and published by the UF Department of Food and Resource Economics, May 2013.